Mutations in the RING domain of TFB3, a subunit of yeast transcription factor IIH, reveal a role in cell cycle progression. - Jona, G; Livi, L; Gileadi, O (2002)
The RNA polymerase II general transcription factor TFIIH is composed of 9 known subunits and possesses DNA helicase and protein kinase activities. The kinase subunits of TFIIH in animal cells, Cdk7, cyclin H, and MAT1, were independently isolated as an activity termed CAK (Cdk-activating kinase), which phosphorylates and activates cell cycle kinases. However, CAK activity of TFIIH subunits could not be demonstrated in budding yeast. TFB3, the 38-kDa subunit of yeast TFIIH, is the homolog of mammalian MAT1. By random mutagenesis we have isolated a temperature-sensitive mutation in the conserved RING domain. The mutant Tfb3 protein associates less efficiently with the kinase moiety of TFIIH than the wild type protein. In contrast to lethal mutants in other subunits of TFIIH, this mutation does not impair general transcription. Transcription of CLB2, and possibly other genes, is reduced in the mutant. At the restrictive temperature, the cells display a defect in cell cycle progression, which is manifest at more than one phase of the cycle. To conclude, in the present study we bring another demonstration of the multifunctional nature of TFIIH.